Additions to the known distribution of Epipompilus aztecus (Cresson, 1869) and E. excelsus (Bradley, 1944) (Hymenoptera: Pompilidae) - Dos Santos, Eduardo Fernando [UNESP]; Noll, Fernando Barbosa [UNESP] (Hindawi, 2010)
Knowledge about the species distribution of Epipompilus Kohl, 1884, is largely based on the records from the species description. Recent efforts in South American bodiversity studies indicate that knowledge about the distribution of Epipompilus species in the region is in an early stage. Two new records of E. aztecus were obtained for the semideciduous Atlantic Forest, in central Brazil, and one record for the Amazonian Forest in northern Brazil, indicating that its distribution extends between Central and South America. The new records of E. excelsus were obtained mainly from the Atlantic Forest highlands, indicating that this species is commonly found in the southeastern South American Central Plateau and restricted to forest ecosystem of this region. © 2010 Eduardo Fernando dos Santos and Fernando Barbosa Noll.
Keywords: Hymenoptera; Pompilidae